PRODUCING OF ERYTHRITOL, 1,2,3-BUTANETRIOL AND 1,2,4-BUTANETRIOL ESTERS WITH PALMITIC, STEARIC, LAURIC AND OLEIC ACIDS (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
New methods for synthesizing polyols have been developed: erythritol, 1,2,3-butanetriol and 1,2,4-butanetriol from 1,4-dichloro-2-butene, 1-chloro-2-butene and 4-chloro-1-butene respectively. The esterification of the resulting erythritol, 1,2,3-butanetriol and 1,2,4-butanetriol with palmitic, stearic, lauric and oleic acids gave the corresponding esters. The physicochemical constants of the obtained compounds are determined. New non-glyceride oil-like products can be used to screen dietary oils and fats.
Keywords: esterification, erythritol, 1,2,3-butanetriol, 1,2,4-butanetriol, stearic, palmitic, lauric and oleic acids